Notes on George Stow’s copy of the Mo’koma (dance of blood) depictions copied from Namahali Shelter, Maloti-Drakensberg - Hollmann, Jeremy; Lombard, Marlize (Southern African Humanities, 2024)
We reintroduce and discuss a painted copy of 16 figures that George Stow recreated from what we refer to as Namahali Shelter. This shelter is located in a part of the Maloti-Drakensberg that is difficult to reach and has not been relocated since Stow’s visit. His comments link the figures, their activities and material culture to the Mo’koma dance described by Arbousset as one of the most important among the San people. Stow’s notes on the figures, the painted copy and the accompanying pencil sketches have not been presented as a cohesive record before. We introduce our own preliminary descriptive notes and interpretations, drawing from current understanding of the San world view. We demonstrate that the depictions from Namahali Shelter are exceptionally rich in conceptual elements that inform their narrative component, allowing us to recognise the interweaving of the ‘real’ with the ‘nonreal’ of some of the elements of the dance. We provide original insight into the possible role of women in healing and out-of-body travel in trance, the use of material culture (such as batons and bored stones), as well as concepts of fighting and death, in the performance of the Mo’koma dance. Our reading remains tentative until Namahali Shelter can be relocated and the original paintings recorded in their complete context.